Metastatic tubercular gummas and splenic tuberculoma secondary to tubercular lymphadenitis in an immunocompetent female. (11th June 2018) - Sanke, Sarita; Chander, Ram; Dalal, Keemi; Agarwal, Shilpi
Abstract: Tubercular gummas and splenic tuberculomas are rare forms of extrapulmonary tuberculosis, usually occurring in immunocompromised individuals. We hereby report a rare combination of multiple tubercular gummas and splenic tuberculoma secondary to TB lymphadenitis in an immunocompetent individual. The patient responded to antitubercular therapy. Thus, in a developing country like ours, tuberculosis can present in a wide clinical spectrum even in an immunocompetent individual.